2007
DOI: 10.1021/bi0620297
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Mechanism of Action of the Antimicrobial Peptide Piscidin

Abstract: Piscidin, an antibacterial peptide isolated from the mast cells of striped bass, has potent antimicrobial activity against a broad spectrum of pathogens in vitro. We investigated the mechanism of action of this 22-residue cationic peptide by carrying out structural studies and electrophysiological experiments in lipid bilayers. Circular dichroism experiments showed that piscidin was unstructured in water but had a high alpha-helix content in dodecylphosphocholine (DPC) micelles. 1H NMR data in water and TFE co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
113
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(120 citation statements)
references
References 54 publications
7
113
0
Order By: Relevance
“…3B). In phosphate buffer, B1, B2, and B3 produced far-UV CD spectra associated with ␣-helical peptides, with ⍜ minima at 222 nm and 205 nm in addition to an apparent maximum at 190 nm (33,34). B4, the "scrambled-sequence" control peptide, maintained a spectrum more closely aligned with a random coil/extended structure with a single minimum at 200 nm (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…3B). In phosphate buffer, B1, B2, and B3 produced far-UV CD spectra associated with ␣-helical peptides, with ⍜ minima at 222 nm and 205 nm in addition to an apparent maximum at 190 nm (33,34). B4, the "scrambled-sequence" control peptide, maintained a spectrum more closely aligned with a random coil/extended structure with a single minimum at 200 nm (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…25,26) In the bacterial system, piscidins have antibacterial activities, which are possibly due to their ability to permeabilize bacterial membranes. 15,27) To investigate the membranepermeabilizing ability of piscidins, we measured the release of the fluorescent marker, calcein, from liposomes of different compositions. We employed neutral charged LUVs composed of 10 : 1 (w/w) PC/cholesterol lipids used for mimicking the major components of the cell membrane of human erythrocytes, and negatively charged LUVs composed of 3 : 1 (w/w) PC/PS to mimic microbial cells.…”
Section: Resultsmentioning
confidence: 99%
“…13,14) Also, its mechanism of action against bacteria was defined as that piscidin is more likely to permeabilize the membrane by toroidal pore formation rather than via the "barrel-stave" mechanism. 15) However, their exact mode of fungicidal action remains unknown.…”
mentioning
confidence: 99%
“…This study was the first one which identified in rodlet cells a host-associated chemical biomarker [157]. All piscidins show broad-spectrum antimicrobial activity, probably killing cells via toroidal-pore formation [151,170,171]. Although attractive as potential candidates for topical application use because of their activity at high salt concentrations [172], the disadvantage of piscidins in this regard is their haemolytic and cytotoxic properties [173].…”
Section: Antimicrobial Peptidesmentioning
confidence: 94%